AN ANALYSIS OF SOCIOLOGICAL ASPECTS IN THE NOVEL BULAN DI LANGIT PEDIR BY AZMI ABUBAKAR: A POTRAIT OF SHARIA AND VARIOUS DEVIANTS OF CULTURAL BEHAVIOR IN ACEH: AN ANALYSIS OF SOCIOLOGICAL ASPECTS IN THE NOVEL BULAN DI LANGIT PEDIR BY AZMI ABUBAKAR: A POTRAIT OF SHARIA AND VARIOUS DEVIANTS OF CULTURAL BEHAVIOR IN ACEH - JANNAH, RAUZATUL; Zuraini, Zuraini (Journal of English Education and Social Science, 2021)
This thesis is a research about An Analysis of Sociological Aspects in Novel Bulan di Langit Pedir by Azmi Abubakar. The objective of the research is to analysis various things that are the cause of why in Aceh which is thick with Islam there can be deviations in cultural behavior that has led to heresy and to find out the impact for Aceh province as a result of deviation that occurred in Acehnese society. The method used in this research is qualitative method. The data resource of this research was the novel “Bulan di Langit Pedir” which was published in 2017. In collecting the data, the researcher used library research, which is a data collection technique taken from library. This technique was done by searching, gathering, reading, and studying all the words, phrases, sentences, paragraphs that reveal structural aspects and problems contained in the novel. In the procedure of data collection, the researcher focused on categorize the data collection into primary data and secondary data. After reading the novel many times, the researcher found and selected the data that was of sentences have language functions and that would relevant to various variants of cultural behavior in Aceh. found and selected the data that the most of sentences have language functions based on its purpose taken from novel that relevance to various deviants of cultural behavior in Aceh and the researcher analysis of intrinsic elements aims to assist in the subsequent analysis process, namely the analysis of socio-cultural problems contained in the novel like the form of crime, cultural deviations, violations of community norms, violations of sharia law and environmental problems in Acehnese society. The research of this research shows in Aceh everything must be done based on sharia and the laws in force in Aceh but many parties have deviant behavior due to several factors such as money, love and contentment. This deviation has consequences for the social condition of Acehnese people. The consequences include the fading of traditional values and changing character of Aceh community. Aceh with religions character has change to hedonism character.